Teacher's Efforts in Improving Students' Mathematics Learning Achievement for Grade 4 Students - Khasanah, Nur Ni'matul; Hariyadi, Rahmat (Universitas Pahlawan Tuanku Tambusai, 2020)
The purpose of this research is to find out how the teacher's efforts in improving mathematics learning achievement of 4th grade students in (Madrasah Ibtidaiyah Negeri) MIN Salatiga and (Madrasah Ibtidaiyah) MI Ma'arif Pulutan Salatiga 2018/2019 school year. This type of research is a qualitative descriptive research using observation, interviews, and documentation to collect data. Data analysis in this research used technical triangulation, time triangulation and source triangulation. The results showed that the teacher's efforts to improve mathematics learning achievement in the 4th grade students in both schools, namely efforts to motivate students by creating a competitive classroom atmosphere, efforts in guiding students through night courses and OSN (Olimpiade Sains Nasional or National Science Olympiad), efforts in the process of implementing learning through the mathematics breakfast method and quiz at the beginning of learning, using varied learning methods and models, use a variety of games in learning and efforts in evaluation namely daily tests, PTS (Penilaian Tengah Semester or Mid-Term Assessment) dan PAS (Penilaian Akhir Semester or Final-Term Assessment).